2018
DOI: 10.1155/2018/1039635
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mask Oxygen Therapy and High-Flow Oxygen Therapy after Cardiopulmonary Bypass in Obese Patients

Abstract: Background To clarify the efficiency of mask O2 and high-flow O2 (HFO) treatments following cardiopulmonary bypass (CPB) in obese patients. Methods During follow-up, oxygenization parameters including arterial pressure of oxygen (PaO2), peripheral oxygen saturation (SpO2), and arterial partial pressure of carbon dioxide (PaCO2) and physical examination parameters including respiratory rate, heart rate, and arterial pressure were recorded respectively. Presence of atelectasia and dyspnea was noted. Also, comfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…We summarized the study and patient characteristics included in the studies in Table I and Table II. Among the included studies, two studies (16,18) were RCTs. The study of Stéphan et al (19) is a post hoc analysis of a predesigned RCT (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We summarized the study and patient characteristics included in the studies in Table I and Table II. Among the included studies, two studies (16,18) were RCTs. The study of Stéphan et al (19) is a post hoc analysis of a predesigned RCT (20).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported the reintubation and the sample size was 255. In the report by Sahin et al (18), the number of reintubation was 0 for the HFNC group and 4 for the COT group. The nosocomial pneumonia reported by Corley et al (16) was 0 for the HFNC group and 1 for the COT group.…”
Section: Dyspnea Score At 24 H Postoperative (Improvement)mentioning
confidence: 90%
“…Ten trials [51][52][53][54][55][56][57][58][59][60] compared prophylactic HFNC to COT and only one trial compared HFNC to NIPPV [61]. Of these, six trials were conducted in patients following cardiac surgery [53,55,57,58], four trials were conducted following thoracic surgery [51,52,56], and one trial was performed in patients after major combined thoracic and abdominal surgery [54]. With the exception of blinding, all trials, except one [52], were judged to be at low or probably low risk of bias.…”
Section: Evidence Summarymentioning
confidence: 99%
“…38 However, none of the studies comparing HFNC with conventional oxygen therapy during and after cardiothoracic surgery reported differences in FEV 1 before and after surgery between groups. 20,21,39 More studies are needed to confirm the relationship between air-flow limitation and length of hospital stay in patients undergoing cardiothoracic surgery. In addition, the criteria for discharge from the hospital were not identical among different medical centers, which might lead to an insignificant difference in the stay between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 8 articles met our inclusion criteria and were selected for data extraction, analysis, and quality assessment. [16][17][18][19][20][21][22][23] A flow chart of the search strategy and the reasons for exclusion are shown in Figure 1.…”
Section: Study Selectionmentioning
confidence: 99%